Integrated Event Tourism Packaging in National Strategic Areas: A Collaborative Planning Model for SAMOTA, Indonesia - Sirajuddin; Ramdah Radjab; Ida Ayu Yadnya Pidada Sari Dewi Utami Pidada; Endang Sri Wahyuni; Rochmah Dewi Suryani (Politeknik Negeri Bandung, 2025)
Purpose: This study aims to formulate and validate an integrated event tourism package planning model for the SAMOTA National Strategic Tourism Area (KSPN) in Sumbawa, Indonesia. It addresses the critical gap in existing destination management, where flagship events and natural attractions are often marketed in silos, limiting their economic impact and sustainability. Design/methodology/approach: The study adopts a Research and Development (R&D) approach utilizing the 4-D Model (Define, Design, Develop, Disseminate). Data were collected through in-depth interviews with penta-helix stakeholders, including government officials, local communities, and cross-regional travel agencies (Lombok, Bali, and Makassar). The resulting model underwent expert validation to ensure feasibility and market relevance. Findings: The research produced a